Technical services today and tomorrow (Libraries Unlimited, 1998)
Focusing on one of the most fundamental areas of librarianship, Gorman and a host of distinguished contributors examine the current state of the field of technical services and offer their views on its future. The book is divided into four sections: acquisitions, bibliographic control, automation, and administration. Within these sections individual chapters address specific aspects of the field (e.g., serials acquisitions, descriptive cataloging, circulation services)